Autofluorescent antimalarials by hybridization of artemisinin and coumarin: in vitro/in vivo studies and live-cell imaging - Herrmann, Lars; Leidenberger, Maria; Sacramento de Morais, Adrielle; Mai, Christina; Çapci, Aysun; da Cruz Borges Silva, Mariana; Plass, Fabian; Kahnt, Axel; Moreira, Diogo R.M.; Kappes, Bärbel; Tsogoeva, Svetlana (Chemical Science, 2023)
Malaria is one of our planet's most widespread and deadliest diseases, and there is an ever-consistent need for new and improved pharmaceuticals. Natural products have been an essential source of hit and lead compounds for drug discovery. Antimalarial drug artemisinin (ART), a highly effective natural product, is an enantiopure sesquiterpene lactone and occurs in Artemisia annua L. The development of improved antimalarial drugs, which are highly potent and at the same time inherently fluorescent is particularly favorable and highly desirable since they can be used for live-cell imaging, avoiding the requirement of the drug's linkage to an external fluorescent label. Herein, we present the first antimalarial autofluorescent artemisinin-coumarin hybrids with high fluorescence quantum yields of up to 0.94 and exhibiting excellent activity in vitro against CQ-resistant and multidrug-resistant P. falciparum strains (IC50 (Dd2) down to 0.5 nM; IC50 (K1) down to 0.3 nM) compared to reference drugs CQ (IC50 (Dd2) 165.3 nM; IC50 (K1) 302.8 nM) and artemisinin (IC50 (Dd2) 11.3 nM; IC50 (K1) 5.4 nM). Furthermore, a clear correlation between in vitro potency and in vivo efficacy of antimalarial autofluorescent hybrids was demonstrated. Moreover, deliberately designed autofluorescent artemisinin-coumarin hybrids, were not only able to overcome drug resistance, they were also of high value in investigating their mode of action via time-dependent imaging resolution in living P. falciparum-infected red blood cells.
CRIS-Team Scopus Importer:2023-11-17

(Iso)Quinoline–Artemisinin Hybrids Prepared through Click Chemistry: Highly Potent Agents against Viruses - Capci Karagöz, Aysun; Lorion, Mélanie M.; Mai, Christina; Hahn, Friedrich; Hodek, Jan; Wangen, Christina; Weber, Jan; Marschall, Manfred; Ackermann, Lutz; Tsogoeva, Svetlana (Chemistry - A European Journal, 2020)
Viral infections cause life-threatening diseases in millions of people worldwide every year and there is an urgent need for new, effective antiviral drugs. Hybridization of two chemically diverse compounds into a new bioactive effector product is a successful concept to improve the properties of a hybrid drug relative to the parent compounds. In this study, (iso)quinoline–artemisinin hybrids, obtained through copper-catalyzed azide–alkyne cycloaddition or metal-free click reactions (in organic solvents or in the presence of water), were analyzed in vitro, for the first time, for their inhibitory activity against human cytomegalovirus (HCMV), relative to their parent compounds and the reference drug ganciclovir. EC50 (HCMV) values were obtained in a range 0.22–1.20 μm, which indicated highly potent antiviral properties in the absence of cytotoxic effects on normal cells (CC50>100 μm). The most active hybrid, 1 (EC50=0.22 μm), is 25 times more potent than its parent compound artesunic acid (EC50=5.41 μm) and 12 times more efficient than the standard drug ganciclovir (EC50=2.6 μm). Interestingly, hybrid 1 also shows inhibitory activity against hepatitis B virus in vitro (EC50 (HBeAg)=2.57 μm).
CRIS-Team Scopus Importer:2020-08-28
Keywords: antiviral agents; artemisinins; click chemistry; cycloaddition; quinolines

Speeding up Viedma Deracemization through Water-catalyzed and Reactant Self-catalyzed Racemization - Tortora, Carola; Mai, Christina; Cascella, Francesca; Mauksch, Michael; Seidel-Morgenstern, Andreas; Lorenz, Heike; Tsogoeva, Svetlana (ChemPhysChem, 2020)
Viedma deracemization is based on solution phase racemization, dissolution of racemic or scalemic conglomerates and crystal growth through autocatalytic cluster formation. With rate limiting racemization, its acceleration by appropriate catalysts may result in speeding up deracemization. A conglomerate-forming chiral compound may principally racemize directly, or via reverse of its formation reaction. For a hydrazine derivative, we investigated available racemization pathways in presence of pyrrolidine or thiourea amine as base catalysts: via Mannich or aza-Michael reaction steps and their reverse, or by enolization. Racemization by enolization was computationally found to dominate, both under water-free conditions and in presence of water, involving a multitude of different pathways. Faster racemization in presence of water resulted indeed in more rapid deracemization, when the base was pyrrolidine. Under water-free conditions, the role of water as enolization catalyst is assumed by chiral hydrazine itself – in autocatalytic racemization and in which both reactant and product are catalysts.
CRIS-Team Scopus Importer:2020-09-04
Keywords: autocatalysis; deracemization; enolization; racemization; stereochemistry

Synthesis of Tamoxifen-Artemisinin and Estrogen-Artemisinin Hybrids Highly Potent Against Breast and Prostate Cancer - Fröhlich, Tony; Mai, Christina; Bogautdinov, Roman P.; Morozkina, Svetlana N.; Shavva, Alexander G.; Friedrich, Oliver; Gilbert, Daniel; Tsogoeva, Svetlana (ChemMedChem, 2020)
In the search for new and effective treatments of breast and prostate cancer, a series of hybrid compounds based on tamoxifen, estrogens, and artemisinin were successfully synthesized and analyzed for their in vitro activities against human prostate (PC-3) and breast cancer (MCF-7) cell lines. Most of the hybrid compounds exhibit a strong anticancer activity against both cancer cell lines – for example, EC50 (PC-3) down to 1.07 μM, and EC50 (MCF-7) down to 2.08 μM – thus showing higher activities than their parent compounds 4-hydroxytamoxifen (afimoxifene, 7; EC50=75.1 (PC-3) and 19.3 μM (MCF-7)), dihydroartemisinin (2; EC50=263.6 (PC-3) and 49.3 μM (MCF-7)), and artesunic acid (3; EC50=195.1 (PC-3) and 32.0 μM (MCF-7)). The most potent compounds were the estrogen-artemisinin hybrids 27 and 28 (EC50=1.18 and 1.07 μM, respectively) against prostate cancer, and hybrid 23 (EC50=2.08 μM) against breast cancer. These findings demonstrate the high potential of hybridization of artemisinin and estrogens to further improve their anticancer activities and to produce synergistic effects between linked pharmacophores.
CRIS-Team Scopus Importer:2020-07-10
Keywords: antitumor agents; artemisinin; breast cancer; estrogen; hybrids; prostate cancer; tamoxifen